Endometrial compaction in patients with chronic endometritis does not predict pregnancy outcomes: a retrospective study - Qingmei Jin; Zhengao Sun; Zhengao Sun; Zizhen Guo; Zizhen Guo (Frontiers in Endocrinology)
BackgroundEndometrial compaction is known to positively influence pregnancy outcomes in patients with infertility undergoing assisted reproductive technology. However, the impact of endometrial compaction on pregnancy outcomes in patients with chronic endometritis following antibiotic treatment is not well understood.Considering the unique characteristics of patients with chronic endometritis, we aimed to investigate whether endometrial compaction predicts pregnancy outcomes during frozen-thawed embryo transfer cycles in this population.MethodsWe enrolled 769 patients who underwent hysteroscopy before frozen-thawed embryo transfer over the past 3 years and subsequently categorized them into the populations with and without chronic endometritis to analyze the impact of endometrial compaction on pregnancy outcomes. To adjust for potential confounding factors, a multifactor binary logistic regression analysis was conducted using clinical co-variables that may have impacted the cycle results.ResultsIn patients with chronic endometritis following antibiotic treatment, endometrial compaction was not significantly associated with biochemical pregnancy (adjusted odds ratio [AOR] = 1.020, 95% confidence interval [CI] = 0.639–1.627), clinical pregnancy (AOR = 1.028, 95% CI = 0.643–1.643), ectopic pregnancy (AOR = 2.003, 95% CI = 0.145–27.635), early pregnancy loss (AOR = 1.356, 95% CI = 0.502–3.663), ongoing pregnancy (AOR = 0.970, 95% CI = 0.600–1.569), and live birth (AOR = 0.881, 95% CI 0.545–1.423). However, endometrial compaction was related to higher rates of clinical pregnancy (AOR = 1.623, 95% CI = 1.052–2.504), ongoing pregnancy (AOR = 2.193, 95% CI = 1.403–3.429), and live birth (AOR = 2.244, 95% CI = 1.431–3.520) in patients without chronic endometritis.ConclusionEndometrial compaction was associated with improved pregnancy outcomes in patients without chronic endometritis but did not predict pregnancy outcomes in those with chronic endometritis, even after antibiotic treatment, suggesting that other factors influence pregnancy success in this population.